Traumatic brain injury and post-acute decline: what role does environmental enrichment play? A scoping review - Frasca, Diana; Tomaszczyk, Jennifer; McFadyen, Bradford J.; Green, Robin E. (Frontiers in Human Neuroscience, 2013)
Objectives: While a growing number of studies provide evidence of neural and cognitive decline in traumatic brain injury (TBI) survivors during the post-acute stages of injury, there is limited research as of yet on environmental factors that may influence this decline. The purposes of this paper, therefore, are to (1) examine evidence that environmental enrichment (EE) can influence long-term outcome following TBI, and (2) examine the nature of post-acute environments, whether they vary in degree of EE, and what impact these variations have on outcomes. Methods: We conducted a scoping review to identify studies on EE in animals and humans, and post-discharge experiences that relate to barriers to recovery. Results: One hundred and twenty-three articles that met inclusion criteria demonstrated the benefits of EE on brain and behavior in healthy and brain-injured animals and humans. Nineteen papers on post-discharge experiences revealed that variables such as insurance coverage, financial, and social support, home therapy, and transition from hospital to home, can have an impact on clinical outcomes. Conclusion: There is evidence to suggest that lack of EE, whether from lack of resources or limited ability to engage in such environments, may play a role in post-acute cognitive and neural decline. Maximizing EE in the post-acute stages of TBI may improve long-term outcomes for the individual, their family and society.